2008
DOI: 10.1039/b803253j
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium amido N-heterocyclic carbene complexes

Abstract: Magnesium dications bind strongly to a tridentate anionic dicarbene ligand L = [N{CH(2)CH(2)(CNCHCHNMes)}(2)] forming dinuclear and trinuclear Mg complexes with some particularly short Mg-C bonds. Treatment of the proligand H(4)LCl(3) with three equivalents of methyl magnesium chloride or benzyl magnesium chloride affords Mg(3)(HL)Cl(6) in high yield. A suspension of in thf was heated to 80 degrees C for 2 h to afford Mg(2)(L)Cl(3), consistent with the loss of one equivalent of MgCl(2), and the deprotonation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 49 publications
(21 reference statements)
1
16
1
Order By: Relevance
“…The Mg(1)-C(1) distances of 2.2931(12) Å (1) and 2.2989(12) Å (2) compare with the longest reported values for Mg-NHC bond lengths (2.153-2.288 Å) 18,19. 1and S9-14 †).…”
supporting
confidence: 68%
“…The Mg(1)-C(1) distances of 2.2931(12) Å (1) and 2.2989(12) Å (2) compare with the longest reported values for Mg-NHC bond lengths (2.153-2.288 Å) 18,19. 1and S9-14 †).…”
supporting
confidence: 68%
“…(NHC 3 = [N{CH 2 CH 2 [NCHCHN(Mes)C]} 2 ], Mes = 2,4,6-trimethylphenyl), 20 are the only other structurally characterised Hauser bases supported by silylated amides. Furthermore, expanding the search to halide Hauser bases of any monodentate amide yields only a handful more examples.…”
Section: }{Mg(cl)}(μ-nhc 3 )(μ-Cl)] and [{Mg(n″)} 2 (μ-Nhc 3 )(μ-Cl)]mentioning
confidence: 99%
“…Of note, tridentate bis(amido)-NHC [NCN] pincer complexes of zirconium and hafnium have been reported, 26,27 and amido-bis(NHC) [CNC] and amido-NHC [C,N] complexes of some early and late transition metals are also known. [28][29][30][31][32][33][34][35] Most closely related to this work, Douthwaite has described the palladium [CNC] complex A and, during the course of our research, Luo has reported the Pd complexes (B). 36,37 Fig .…”
Section: Introductionmentioning
confidence: 99%